Non-Arabic Languages in the Qur'an according to as-Suyuti, Ibn al-Subki and al-Khafiz Ibn Hajar - Murdiono, Murdiono (IAIN Salatiga, 2020)
This research aims to describe non-Arabic languages in the Qur’an according to the scholars who agreed on mu'arrab namely as-Suyuti, Ibn al-Subki and al-Khafiz Ibn Hajar and to reveal the meaning of the word including ta’rîb in the Qur’an. It uses library research method and descriptive qualitative technique analysis with structural, historical, and ideological approaches for the data analysis technique. The results of the study show that: 1) Factors which influence the occurrence of ta’rîb in Arabic especially in the Qur’an are the historical factors, namely geographical proximity, trading relations, immigration, political power, religious tendencies, culture, economy, and industry with other nations. 2) Arabic grows and develops with its closest Semitic languages, such as Habsyah, Aramiah and Akadiah so it will indirectly lead into language and cultural shift. 3) In as-Suyutimadhzab, including Ibn al-Subki, and al-Khafiz Ibn Hajar, believe in the existence of mu'arrab and ta’rîb in the Qur'an, so he collected around 125 non-Arabic words in the Qur'an which consists of 13 languages, including Persian, Habsyah, Hebrew, Suryaniyah, Nabathea, Berber, Zinjiyah, Jewish, Roman, Indian, Saizalah, Turkish and Magrib which are distributed in 41 surahs of the Qur’an.